Особливості виховання креативності старших дошкільників засобами дослідницької діяльності - Онушко, Наталія Сергіївна (My University, 2024)
Тема кваліфікаційної роботи «Особливості виховання креативності старших дошкільників засобами дослідницької діяльності» досліджувалася на теоретичному та емпіричному рівнях. Результати вивчення представлено у двох розділах роботи. На теоретичному рівні схарактеризовано стан розробки проблеми вітчизняними та зарубіжними фахівцями; визначено зміст та структуру провідної категорії; розкрито особливості розвитку творчих здібностей у дошкільному дитинстві; обґрунтовано педагогічні умови оптимізації процесу виховання креативності у закладі дошкільної освіти. З метою розв’язання емпіричних завдань дослідження розроблено програму й методику констатувального експерименту; визначено критерії, показники та структурні компоненти вихованості у дітей 5–7 років креативності; описано рівні сформованості даної якості у досліджуваних старшого дошкільного віку; розроблено систему формування креативності, обґрунтовано педагогічні умови оптимізації освітнього процесу, розкрито методи виховання даної інтелектуальної якості у дітей 5–7 років.
The topic of the qualification work "Peculiarities of raising the creativity of older preschoolers by means of research activities" was studied at the theoretical and empirical levels. The results of the study are presented in two sections of the work. At the theoretical level, the state of development of the problem by domestic and foreign specialists is characterized; the content and structure of the leading category are defined; the peculiarities of the development of creative abilities in preschool childhood are revealed; the pedagogical conditions for optimizing the process of nurturing creativity in the preschool education institution are substantiated. In order to solve the empirical tasks of the research, the program and methodology of the ascertaining experiment were developed; the criteria, indicators and structural components of education in children of 5-7 years of creativity are determined; the levels of formation of this quality in the studied older preschoolers are described; a system for the formation of creativity was developed, the pedagogical conditions for optimizing the educational process were substantiated, and the methods of raising this intellectual quality in children aged 5–7 were revealed. Keywords: personal development, creative activity, creativity as a basic personality quality, optimization of the educational process, creation of a developmental environment.
Keywords: особистісний розвиток; творча діяльність; креативність; оптимізація освітнього процесу; створення розвивального середовища